Application of Article 12 of the 1980 Hague Convention on the Civil Aspects of International Child Abduction in Lithuanian Courts - Limantė, Agnė (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English]The article analyses Article 12 of the 1980 Hague Convention on the Civil Aspects of International Child Abduction which allows courts to refuse return of abducted child where the proceedings have been commenced after the expiration of the period of one year after abduction and it is demonstrated that the child has settled well in the new environment. The author of the article seeks to establish whether the jurisprudence of Lithuanian courts interpreting and applying this Article is well-founded.SummaryThis article scrutinises content and application of the Article 12 of the 1980 Hague Convention on the Civil Aspects of International Child Abduction, in particular its paragraph 2, which allows court to refuse return of abducted child where the proceedings have been commenced after the expiration of the period of one year after abduction and it is demonstrated that the child is now settled in its new environment. The author of the article seeks to establish whether the jurisprudence of Lithuanian courts applying this Article is proper and in line with the Convention.Analysing the cases of national courts of Lithuania, the author of this article established that in several cases Lithuanian courts when interpreting one year term have consistently ruled, that this is a procedural and formal requirement and can be ignored for the best interests of the child. As a result, a child, which is abducted just few months ago is not returned as if is established he has integrated in the country and it is in his/her best interests to continue residing here. The author criticises such an approach and suggests that such practice should be changed.
Keywords: 1980 Hague Convention; child abduction; non-return order